(untitled) (Journal of Educational Sciences, 2019)
The importance to the affective domain in learning is underscored in many research pursuits at the expense of the cognitive development of students studying science, in particular, physics. The thesis has proposed a structure, the pedagogical technological combined medium (PTCM) founded on the electronic model, that builds on the existing premises of pedagogy, content, and technology to make space for the affective domain where these three premises intersect with each other. Establishment of the PTCM framework through a multi-loop model that explores the affective dimension as an overarching space for interaction among learners, teachers, and parents through a series of stages included home tasks, as well as seminar and out-of-university activities. The paper is wanted to show the effectiveness of the methods and techniques of teaching «Electromagnetism». The context provides the results of new technological education teaching, samples the needed literature, and also to bond strengthen the scientific research. Key words: education, teaching, modern education technology, electromagnetism.